PENGARUH KOMPETENSI, PEMAHAMAN TENTANG KODE ETIK, PENGHARGAAN FINANSIAL DAN PERSONALITAS AUDIT TERHADAP MINAT MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIER SEBAGAI AUDITOR INTERNAL (STUDI EMPIRIS PADA MAHASISWA AKUNTANSI UNIVERSITAS MARITIM RAJA ALI HAJI) - Siti Nurfaiza; Jack Febriand Adel; Nurul Yusyawiru (CV. Denasya Smart Publisher, 2026)
Choosing a career is a crucial decision for accounting students, especially given the imbalance between the number of graduates and the number of active internal auditors in Indonesia. This study aims to analyze the influence of competence, understanding of the code of ethics, financial rewards, and audit personality on accounting students' interest in choosing a career as an internal auditor. The research employs a quantitative approach with a descriptive comparative method. The population in this study were accounting students at Raja Ali Haji Maritime University (UMRAH), specifically from the 2021, 2022, and 2023 cohorts. The sample consisted of 115 respondents selected using purposive sampling criteria (students who have taken or are taking auditing courses). Data analysis was performed using Multiple Linear Regression with SPSS. The results showed that Competence, Understanding of the Code of Ethics, and Financial Rewards partially had a significant positive effect on students' interest in becoming internal auditors. However, Audit Personality did not have a significant effect on career interest. Simultaneously, all independent variables influenced the dependent variable with an Adjusted R Square of 77.8%. These findings imply that students prioritize technical skills, ethical understanding, and financial incentives over personality traits when considering this career path.